Angiotensin II Protects Primary Rat Hepatocytes against Bile Salt-Induced Apoptosis - Karimian, Golnar (Public Library of Science, 2012)
Angiotensin II (AT-II) is a pro-fibrotic compound that acts via membrane-bound receptors (AT-1R/AT-2R) and thereby activates hepatic stellate cells (HSCs). AT-II receptor blockers (ARBs) are thus important candidates in the treatment of liver fibrosis. However, multiple case reports suggest that AT-1R blockers may induce hepatocyte injury. Therefore, we investigated the effect of AT-II and its receptor blockers on cytokine-, oxidative stress- and bile salt-induced cell death in hepatocytes. Primary rat hepatocytes were exposed to TNF-α/Actinomycin D, the ROS-generating agent menadione or the bile salts: glycochenodeoxycholic acid (GCDCA) and tauro-lithocholic acid-3 sulfate (TLCS), to induce apoptosis. AT-II (100 nmol/L) was added 10 minutes prior to the cell death-inducing agent. AT-1R antagonists (Sartans) and the AT-2R antagonist PD123319 were used at 1 µmol/L. Apoptosis (caspase-3 activity, acridine orange staining) and necrosis (Sytox green staining) were quantified. Expression of CHOP (marker for ER stress) and AT-II receptor mRNAs were quantified by Q-PCR. AT-II dose-dependently reduced GCDCA-induced apoptosis of hepatocytes (−50%, p<0.05) without inducing necrosis. In addition, AT-II reduced TLCS-induced apoptosis of hepatocytes (−50%, p<0.05). However, AT-II did not suppress TNF/Act-D and menadione-induced apoptosis. Only the AT-1R antagonists abolished the protective effect of AT-II against GCDCA-induced apoptosis. AT-II increased phosphorylation of ERK and a significant reversal of the protective effect of AT-II was observed when signaling kinases, including ERK, were inhibited. Moreover, AT-II prevented the GCDCA-induced expression of CHOP (the marker of the ER-mediated apoptosis). CONCLUSION: Angiotensin II protects hepatocytes from bile salt-induced apoptosis through a combined activation of PI3-kinase, MAPKs, PKC pathways and inhibition of bile salt-induced ER stress. Our results suggest a mechanism for the observed hepatocyte-toxicity of Sartans (angiotensin receptor blockers, ARBs) in some patients with chronic liver injury.